PENGARUH ANKLE PUMPING EXERCISE TERHADAP PENURUNAN DISUSE ATROFI OTOT PLANTAR FLEXOR (Medial Gastrocnemius dan Soleus) PADA PASIEN FRAKTUR FEMUR - Utami, Kristianti (Coping: Community of Publishing in Nursing; Vol 2 No 2 (2014): JURNAL EDISI MEI-AGUSTUS 2014, 2014)
Fracture is a one of orthopedics problem that often encountered in the health care center. Skin traction is one of femur’s fracture management that often performed in Hospital. Immobilization caused by the using of skin traction causing some complication including disuse atrophy of muscle which health care workers may not pay attention. One of disuse muscles atrophy prevention is ankle pumping exercises. The purpose of this study was to identify the effect of ankle pumping exercises on the descent of plantar flexor muscles disuse atrophy in femur fracture patients with skin traction. This study used quasi experimental design with nonequivalent control group approach which consists of 2 groups: control group and intervention group with 10 samples in each groups using purposive sampling technique. After data collection, the data were analyzed by computer’s program with 95% confidence level. Pretest and posttest calf circumference data of control and intervention groups were analyzed by Shapiro Wilk and the result all data were normally distributed and analysis can proceed with parametric test. Paired sample t-test’s result of control and intervention groups showed diversification between pretest and posttest value with significance value 0,000 and 0,0035. Independent sample t-test of control and intervention groups showed the diversification of control and intervention group with significance value 0,006, thus it can be concluded that there are effects of ankle pumping exercises on the descent plantar flexor muscle’s disuse atrophy. Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;}
Keywords: Femur’s Fracture; Muscle’s Disuse Atrophy; Plantar Flexor’s Muscle; Ankle Pumping Exercises